Beta Burr type X with application to rainfall data - Khaleel, Munddher Abdullah; Ibrahim, Noor Akma; Shitan, Mahendran; Merovci, Faton; Rehman, Erum (Institute for Mathematical Research, Universiti Putra Malaysia, 2017)
We introduce a new extension distribution for Burr type X with one parameter named the Beta Burr type X. The new distribution is extended from the Burr type X with one parameter. Several important properties of the new extension distribution are derived like the moment, and moment generating function. The maximum likelihood estimation is used to estimate the parameters involved. A rainfall data set from 1975 to 2005 for 35 stations in peninsular Malaysia is used for the application of this new model. It gives a better fit compared to several other distributions.